1997
DOI: 10.1071/pp96064
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nitrate in the Osmotic and Nutritional Control of Plant Development

Abstract: I postulate that certain of the effects of nitrate on plant development are mediated by the combination of an osmotic effect on water uptake and a nutritional effect on protein synthesis. This hypothesis is discussed with reference to effects on seed germination, apical dominance, lateral root initiation, flowering and leaf senescence. The postulated osmotic effect of nitrate is consistent with the well-established role of both nitrate and reduced forms of N as major osmotica in plant cells, and also with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
1
5

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 118 publications
4
36
1
5
Order By: Relevance
“…The N supply has frequently been shown to increase the water content, which is related to the contribution of accumulated nitrate and accompanying cations (mostly K + ) to the osmotic potential. 12 However, this effect on the water homeostasis was not observed in the current experiment (results not shown).…”
Section: Results and Discussion Plant Growth And Nutritional Statuscontrasting
confidence: 63%
“…The N supply has frequently been shown to increase the water content, which is related to the contribution of accumulated nitrate and accompanying cations (mostly K + ) to the osmotic potential. 12 However, this effect on the water homeostasis was not observed in the current experiment (results not shown).…”
Section: Results and Discussion Plant Growth And Nutritional Statuscontrasting
confidence: 63%
“…This prompts us to propose that, rather than a nutritional function in seed maturation, this nitrate plays either a signaling or osmotic role during the first steps of imbibition. The role of nitrate in the osmotic control of plant development has already been suggested (McIntyre, 1997). In barley seeds, exogenous nitrate increased water uptake by the seedling (Lieffering et al, 1996).…”
Section: Discussionmentioning
confidence: 98%
“…Ma et al (1997) suggested that the delay in flowering time could be due to the slower leaf emergence, as the nonfertilized plants had lower growth rate. However, the mechanisms underlying the flower induction effect had not been determined, although some studies proposed that N and carbohydrate may contribute to floral induction by an osmotic effect on water uptake (McIntyre 1997).…”
Section: Discussionmentioning
confidence: 99%